Optimalisasi Pelatihan Transparansi Keuangan Masjid Melalui Implementasi Aplikasi Kas Digital - Abdul Karim; Bangun, Budianto; Prayetno, Sugeng Prayetno; Afrendi, Mohammad (Forum Kerjasama Pendidikan Tinggi, 2025)
Transparent and accountable financial management is essential for maintaining congregational trust and enhancing participation in religious and social activities. However, many mosques still manage their finances manually, making them prone to recording errors and lack of transparency. This community service activity aims to optimize financial transparency in mosques through the implementation of the eKasMasjid digital cash application, accessible online via http://ekasmasjid.com. The methods involved include socialization, training for mosque administrators on how to use the application, and continuous mentoring and evaluation during implementation. The results show that the eKasMasjid application significantly improves financial recording efficiency, reduces transaction errors by up to 85%, and facilitates financial reporting that can be accessed openly by the congregation. A survey of mosque congregants revealed that 89% expressed increased trust in the mosque’s financial management, and 76% felt more motivated to donate regularly. In conclusion, the use of digital technology through the eKasMasjid application contributes positively to establishing a more transparent, accountable, and participatory mosque financial governance system.